Analogism, animism, and naturalism in Los ríos profundos - López Maguiña, Santiago (2024)
The present work is an approach to the modes of analogical, animistic and naturalistic identification in Los ríos profundos. They are notes of an ongoing semiotic research with which we intend to open unexplored avenues. A concern emerges: to what extent can the aforementioned modes be precisely distinguished in the novel?